TINGKAT STATUS GIZI BERDASARKAN BODY MASS INDEKS DI SDN 2 KRINJING MAGELANG PASCA BENCANA MERAPI - Pritama, Muhammad Atiq Noviudin; Astuti, Amilla Fidyah (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2016)
Revealed that the nutritional state of a person is a picture of what is consumed in the long term. Nutrition condition canmanifest less or more. Levels of malnutrition can be mild, moderate or severe. Likewise, the state of nutrition can be mild,moderate or severe. Someone who lack one or more nutrients can cause a deficiency disease. Only mild deficiency can causedecreased ability to function although sometimes not realized it was due to nutritional factors. In accordance with the theoryof food food become essential to the survival of a person in accordance with the functions of food, so oraang must understandwhat is needed for the body and food functions. Children in the age of 5-8 years is a golden period in which the child shouldbe provided with sufficient food nutrition as foundation or baseline for survival that will come without experiencing interferencewill disrupt the process of development of the child because that age is included vulnerable nutritional need attention important.Vulnerable nutrition usually occurs in infants, toddlers, school children 6-13 ye hypertension, coronary heart, diabetes andstroke. Other terms submitted by Michael J. Gibney et al (2005: 304) A small child underweight was sh ort (stunted), irondeficiency, smallish by age gestasionalnya. (SGA, small for gestational age) or up to a lower level, it can show the deficiency zineperubahn behavior. Therefore, the need to pay attention to the nutritional status of the existing on-age children of school ageespecially SDN N 2 Krinjing has experienced a catastrophic eruption of Mount Merapi in 2010 ago that after the accidentoccurred nutritional status is there to say good nutritional status as it should be. SDN 2 Krinjing Magelang district needsto do research after experiencing a catastrophic eruption of Mount Merapi in 2010 ago for school age range, especially intonutritional status for the survival of both growth and development when it comes to survival. Knowing the nutritional statusby measuring BMI (Body Mass Index) in SDN 2 Krinjing Magelang Merapi disaster and Knowing the number of childrenclassified as more nutritional status and malnutrition by taking the measurements of BMI (Body Mass Index) in SDN 2Krinjing Magelang Merapi disaster. So that the nutritional status of the SDN 2 Krinjing Magelang district in accordancewith the data presented in the results of the study showed undernutrition or underweight status and rightly need to be addressed,which means before the happening things that are not desirable. Thus, BMI is one tool used in obtaining data on nutritionalstatus can be said to be appropriate for a person is his body balanced or normal is balanced between weight and height so thatthe interconnections between them, and as a benchmark to become a benchmark in status nutrition.